Evaluasi Program Pembelajaran Kurikulum Merdeka di Ma’had Utsman bin ‘Affan Binbaz 25 Jambi - Irawan, Dedy; Sari, Fiqi Nurmanda; Shodikin, Eko Ngabdul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to evaluate the implementation of the Merdeka Curriculum learning program at Ma'had Utsman bin 'Affan BINBAZ 25 Jambi. The aspects evaluated include: planning, implementation, and learning evaluation. The method used in this research is descriptive qualitative. The subjects in this research were 4 teachers, Ma'had Utsman bin 'Affan BINBAZ 25 Jambi, and 4 students. The data were analyzed using critical analysis techniques, with the Miles and Huberman model through data reduction, data presentation, and data verification. The results of the research show that the evaluation process for the Merdeka Curriculum Learning Program at Ma'had Utsman bin 'Affan BINBAZ 25 Jambi has not been implemented optimally. This can be seen from educators who 100% have not made teaching modules in the learning process, 50% of teachers who do not provide teaching materials in the form of learning media, 75% of teachers who do not create small groups in learning, and 75% of teachers who use objective and subjective tests.